Rancang Bangun Sistem Informasi Pengajuan Asuransi Di PT. Unity Corporation Berbasis Web - Indra, Indra; Sudarsono, Bernadus Gunawan; Bani, Alexius Ulan (Journal of Engineering, Technology and Computing (JETCom), 2024)
PT Unity Corporation, operating in the fields of health insurance, life insurance, education insurance, and other types of insurance in South Jakarta, faces issues with insurance registration that still relies on paper forms. These paper forms are susceptible to damage such as tearing or wetting during transport from the applicant's home to the company's office, as well as the risk of loss by agents. This research aims to design and develop a web-based insurance application system to address these issues. The development method used is Waterfall, with MySQL for data management, and testing is conducted using the Black Box method to ensure system functionality. The outcome of this research is a user interface (UI) and application prototype that has been tested and shows favorable results. It is expected that this system will enhance the efficiency of the insurance registration process, reduce the risk of loss or damage to documents, and provide significant benefits to both the company and its customers.